2021
DOI: 10.3389/fphys.2021.685306
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acute Aerobic Exercise on Blood Pressure, Arterial Function, and Heart Rate Variability in Men Living With HIV

Abstract: PurposeThis study aims to investigate the effects of acute cycling on blood pressure (BP), arterial function, and heart rate variability (HRV) in men living with HIV (MLHIV) using combined antiretroviral therapy (cART).MethodsTwelve MLHIV (48.7 ± 9.2 years; 25.2 ± 2.8 kg m–2) and 13 healthy controls (41.2 ± 9.9 years; 26.3 ± 2.9 kg m–2) performed a cycling bout (ES) (intensity: 50% oxygen uptake reserve; duration: time to achieve 150 kcal—MLHIV: 24.1 ± 5.5 vs. controls: 23.1 ± 3.0 min; p = 0.45), and a 20-min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
2
3
0
Order By: Relevance
“…after the exercise. The increase in pulse rate in this study agrees with the findings of Barros et al (2021), who reported increased heart rates of subjects after bouts of aerobic exercise. This study is in agreement with the report of the Centre for Disease Control on blood pressure changes after aerobic exercise (Kim and Kang 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…after the exercise. The increase in pulse rate in this study agrees with the findings of Barros et al (2021), who reported increased heart rates of subjects after bouts of aerobic exercise. This study is in agreement with the report of the Centre for Disease Control on blood pressure changes after aerobic exercise (Kim and Kang 2019).…”
Section: Discussionsupporting
confidence: 92%
“…contrary, Barros et al (2021) reported decreased systolic blood pressure in normal individuals after exercise, which agrees with other studies (Pinto et al 2006;Cardoso et al 2010;Perrier-Melo et al 2020). The decrease in blood pressure reported could be due to post exercise recovery: This post exercise hypotension could be due to the intensity, volume or duration of the exercise (Brito et al 2018;Fonseca et al 2018).…”
supporting
confidence: 87%
“…Although sympathoinhibition likely occurs postexercise, its role in prolonged BP reductions is unclear. Primary trials across diverse populations reported increased sympathetic and/or reduced vagal activity with PEH [15,18,19,[55][56][57][58][59][60]. Recent meta-analyses observed parallel increases in sympathetic and/or decreases in parasympathetic modulation after both aerobic and resistance exercise, contrary to expectations, irrespective of resting BP [52,35].…”
Section: Potential Central Mechanisms Of Postexercise Hypotensionmentioning
confidence: 94%
“…According to the incidence of cancer patients with AIDS, Kaposi’s sarcoma, non-Hodgkin’s lymphoma, and invasive cervical cancer were classified as AIDS-related tumors by the CDC in the US in 1993. 1 KS is the most common malignant tumor related to AIDS, which is vascular endothelial cells characterized by red or purple-brown maculopapular lesions. KS can occur alone or involve the oral gastrointestinal tract and respiratory systems.…”
Section: Introductionmentioning
confidence: 99%